Studying the history and culture of Ukraine as a means of forming intercultural communicative competence among international students - Bondarenko, H. (Teaching Languages at Higher Educational Establishments at the Present Stage. Intersubject Relations, 2025)
The article is devoted to substantiating the role of studying the history and culture of Ukraine as a key factor in forming intercultural communicative competence among international students in higher education. The study analyses contemporary academic approaches to the structure of intercultural communication and establishes that language training alone cannot ensure a full understanding of sociocultural norms without integrating materials of historical and cultural content. The relevance of the work is determined by the need to update methodological approaches to the training of international students, to strengthen the role of humanities in developing intercultural dialogue, and to overcome cultural barriers in the learning process. Teaching the history of Ukraine and Ukrainian culture to international students acquires particular significance, as it performs not only an educational but also an important image-building function, contributing to the formation of a holistic understanding of Ukraine in the global context. The purpose of the article is to determine the importance of cultural and historical training of international students as a necessary condition for effective intercultural interaction, which ensures a deeper understanding of the semantic, pragmatic, and contextual features of communication in Ukrainian society. The methodological basis of the study is an interdisciplinary approach that combines developments in intercultural communication theory, cultural studies, and educational anthropology. To clarify the impact of the cultural component on the formation of intercultural communicative competence, the study employs the method of structural-functional analysis and elements of pedagogical observation. The obtained results demonstrate that materials on the history, culture, and national traditions of Ukraine contribute to forming a holistic cultural perspective, expand the context of educational interaction, enhance motivation, and create conditions for the development of communicative flexibility. It is revealed that systematic work with cultural meanings and value orientations significantly strengthens studentsʼ ability to interpret cultural differences, increases tolerance, and ensures more effective adaptation to the Ukrainian sociocultural environment. The findings have practical significance for developing methodological recommendations and curricula aimed at improving the system of intercultural training of international students under conditions of university internationalization.